Physics of the future : how science will shape human destiny and our daily lives by the year 2100 - Kaku, Michio (New York : Doubleday, 2011)
Explains how science will shape human destiny and everyone's daily life by the year 2100. Kaku gives a picture of the coming century based on interviews with over three hundred of the world's top scientists who are already inventing the future in their labs.
Predicting the next 100 years -- Future of the computer : mind over matter -- Future of AI : rise of the machines -- Future of medicine : perfection and beyond -- Nanotechnology : everything from nothing? -- Future of energy : energy from the stars -- Future of space travel : to the stars -- Future of wealth : winners and losers -- Future of humanity : planetary civilization -- A day in the life in 2100.
Includes bibliographical references (pages 377-378) and index.
Keywords: Science -- Social aspects -- Forecasting; Science -- History -- 21st century; Science; Science -- Social aspects -- Forecasting; Science -- Social aspects; Science -- Forecasting; 2000-2099; History